Don't worry, I had a bunch of trouble with this, too.
y = x + 4
y = −2x − 2
Basically, you substitute y for x+4.
Real quick, you know how if you have a problem like, [ y = 3x + 5 ], you're told that x = 2, then solve for y? Substatute basically means replace. So when you're replacing x with 2, your substituting x for 2. The problem you've shown is just a little more complicated.
So you start with this problem:
y = x + 4
y = −2x − 2
Then you replace one y with what the other one is equaled to.
So you end up with something like this:
x + 4 = −2x − 2
Then just solve :)
3x = -6
x = -2
I hope this helps! :D Feel free to ask any questions.
And please, only if you think I deserve it, it would help a bunch if you marked this answer as branliest!